Anti‐allergic effect of ascorbic acid derivative DDH‐1 in a mouse model of atopic dermatitis. Issue 8 (25th April 2022) - Kitahata, Kosuke; Matsuo, Kazuhiko; Sato, Masako; Susami, Yoko; Hara, Yuta; Morikawa, Toshio; Oiso, Naoki; Kawada, Akira; Otsuka, Atsushi; Nakayama, Takashi
Abstract: Atopic dermatitis (AD) is the most common inflammatory skin disease, which is characterized by excessive Th2 immune responses. In AD patients, the expression of the chemokines CCL17 and CCL22 is increased in skin lesions, leading to the infiltration of Th2 cells. In addition, typical pro‐inflammatory cytokines, including TNF‐α, IL‐1β and IL‐6, have also been shown to be associated with the pathogenesis of AD. Recently, DDH‐1, an ascorbic acid derivative, has been synthesized and demonstrated to have a more stabilized structure and better skin penetrability. Furthermore, DDH‐1 has been shown to suppress pro‐inflammatory cytokine expression in vitro and in vivo. Therefore, using an AD mouse model, we evaluated the effect of DDH‐1 to reduce allergic skin inflammation. We found that cutaneous administration of DDH‐1 significantly reduced the expression levels of TNF‐α, IL‐1β and IL‐6 in the skin lesions of AD‐like mice. Additionally, DDH‐1 administration also significantly reduced the expression levels of CCL17 and CCL22, resulting in decreased skin infiltration of Th2 cells. Consequently, DDH‐1 reduced ear and epidermal thickness, the serum IgE levels and the number of infiltrating inflammatory cells and mast cells into the AD‐like skin lesions. Combination treatment with DDH‐1 and corticosteroid more efficiently improved the skin lesions compared with corticosteroid alone. Collectively, our results suggest that DDH‐1 has an anti‐allergic effect in an AD mouse model by reducing not only the pro‐inflammatory cytokine expression but also the Th2‐associated chemokine expression. Thus, DDH‐1 may be beneficial for AD treatment and prevention as a monotherapy or in combination with corticosteroids.